An Efficient Needleless Grasping Suture Technique for Graft Preparation in Anterior Cruciate Ligament Reconstruction - Fang, Chaohua; Cheng, Rongshan; Jiang, Jian; Dimitriou, Dimitris; Wang, Huizhi; Jiang, Ziang; Tsai, Tsung-Yuan; Cheng, Cheng-Kung (Frontiers in Surgery, 2022)
Objective: Several needleless techniques have been developed to outcome the inherent disadvantages of the traditional needle stitching technique for graft preparation, such as tendon damage through the needle, time consumption, and the potential risk of needlestick injury. The purpose of the present study was to compare the graft preparation time and the biomechanical performance between an efficient needleless technique and the traditional needle stitching technique for graft preparation in anterior cruciate ligament reconstruction (ACLR). Methods: The time required to perform a complete suture on 20 hamstring tendons (HTS) during ACLRs was measured. The grafts from one side were prepared using the needle stitching technique. The grafts from the other side used the needleless grasping suture technique. For the second part of the study, 12 fresh-frozen porcine flexor tendons were divided into two groups using two techniques and were mounted in an electric tensile test system. Each group was pretensioned to 100 N to simulate the maximum initial graft tension. The suturing state of sutures and graft (intact and damaged) and the load-elongation curve were recorded for each group. A Student’s t-test was used to compare the means of two groups. Results: In operation, the needleless grasping suture technique group (19.8±4.8, range: 13.5 to 32.9 s) was significantly faster (p<0.05) than the needle stitching technique group (52.7±12.7, range: 36.0 to 87.5 s). The state of sutures in each group was intact. The mean elongation was 11.75±1.38 (range: 9.47–12.99) mm and 10.59±1.02 (range: 9.12–11.76) mm in the needleless stitching technique group and the needle grasping suture technique group, respectively. There was no statistically significant difference in the elongation between the two groups (p>0.05). Conclusions: The needleless grasping suture technique was a convenient and efficient method for graft preparation in ACLR.